FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA (Media Riset Akuntansi, 2022)
Earnings management is management of behavior for profit in accordance with his wishes and actions taken by management. This research aims to test and analyze firm size, profitability, leverage, and commissioner independent on earning management. The population in this study was the Mining Company which was listed on the Indonesia Stock Exchange in the period 2015- 2018, which amounted to 168 companies and the sample used amounted to 56 companies. The sampling technique used in the study was the purposive sampling method. The analytical method used is multiple linear regression using SPSS 24 software. The results show that the profitability the earnings management. While firm size, leverage, and commissioner independent have no effect on earnings managem